Association of possible Sarcopenia, Sarcopenia and sarcopenic obesity with multimorbidity among middle-aged and older adults: findings from the China health and retirement longitudinal study - Kaixin Zhang; Xiaowei Zheng; Tao Ma (Archives of Public Health)
Abstract Background and objectives The association between possible sarcopenia, sarcopenia and sarcopenic obesity on multimorbidity risk remains poorly investigating. We aimed to evaluate the associations between possible sarcopenia, sarcopenia and sarcopenic obesity on multimorbidity prevalence and incidence among middle-aged and older Chinese population. Methods A total of 13,036 participants from the China Health and Retirement Longitudinal Study 2011 were included in cross-sectional analyses. 5771 participants were including in longitudinal analyses and were followed up in 2018. Sarcopenia status was defined according to the Asian Working Group for Sarcopenia 2019 (AWGS 2019) criteria. Obesity was defined according to body mass index. Results In cross-sectional analyses, possible sarcopenia, sarcopenia and sarcopenic obesity were significantly associated with higher multimorbidity prevalence. During the 7 years of follow-up, 2295(39.77%) participants with new-onset multimorbidity were identified. Compared with participants without sarcopenia or obesity, a greater increase in the risk of multimorbidity incidence was found among participants with obesity only (OR = 1.39, 1.21–1.59), sarcopenia only (OR = 1.45, 1.35–1.58) and sarcopenic obesity (OR = 2.42, 2.03–2.89). Both pre-sarcopenia, sarcopenia and sarcopenic obesity were positively related to an increased number of morbidities. Conclusion Pre-sarcopenia, sarcopenia and sarcopenic obesity were associated with higher multimorbidity prevalence and incidence. Our findings provide important implications for screening and preventing possible sarcopenia, sarcopenia and obesity, which may be beneficial in reducing chronic disease burden.